Enhancing Customer Loyalty: The Mediating Effect of Experience on Usability, Security, and Content Quality with Digital Literacy Moderation - Sandi Setiadi (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
In the rapidly evolving digital landscape, retaining customer loyalty has become a critical challenge for businesses. This research addresses the challenge of sustaining customer loyalty in the digital era by examining how ease of use, security, and content quality affect it. The study’s purpose is to examine customer experience as a mediator and digital literacy as a moderator within this context. Employing an explanatory quantitative method focused on digital service users in West Java, the data were evaluated using Structural Equation Modeling (SEM-PLS). The findings indicate that the model possesses a remarkably high predictive capability, specifically 95.6% for the customer loyalty variable. The key discoveries highlight that ease of use, security, and content quality exert a direct and significant influence on loyalty, with content quality emerging as the most influential factor. Conversely, this article discusses that customer experience is not proven to mediate this relationship, and digital literacy does not perform a moderating function. This provides a significant contribution that the functional effectiveness and substance of information are more decisive in user loyalty than the complex experience evaluation process in this model.